HUBUNGAN TINGKAT KELELAHAN SUBJEKTIF DENGAN PRODUKTIVITAS PADA TENAGA KERJA BAGIAN PENGEMASAN DI CV SUMBER BAROKAH - Lince Verawati (The Indonesian Journal of Occupational Safety and Health, 2016)
Work fatigue is a subjective feeling followed by declining of efficiency and desire to work. Fatigue can also result in work accident which affect directly to productivity. The purpose of this research was know the relation between subjektive fatigue and labor’s productivity at packaging division of chip factory, CV Sumber Barokah. This study was a descriptive study with cross sectional design. Samples were taken with a total sampling principle that all workers from packaging division who totaled 27 people. The variables were years of working life, nutritional status and subjektive fatigue and labor’s productivity. The data obtained were analyzed descriptively using Contingency Coeffisient. The results showed that the most of the respondents were 1-2 years of working life, had better nutritional status. The result of fatigue measurement used the checklist which indicated that respondents medium fatigue caused work hours and breaktime is not accordance with provision of labour laws. Respondents can package the chip based on target. The results showed existence between fatigue with labor’s productivity. The association values were 0,798 susceptible values from 0.50 to 0.75 which means a moderate level of relationship. The conclusion shows the relation between fatigue with labor’s productivity. My suggestion for the corporation is performing work hours and break time in accordance with provision of labour laws number 13 of 2003.Keywords: subjektive fatigue, labor’s productivity